Availability, Utilization, And Contribution of Students Health Services at Tertiary Institutions in Sokoto, Nigeria - Hiliya, Abbas Abubakar; Yahaya, Abubakar (Lembaga Yasin AlSys, 2025)
This study examines the availability, utilization, and contribution of students' health services at tertiary institutions in Sokoto, Nigeria. A survey research design was employed, and data were collected from 400 students and staff of selected tertiary institutions. The results show that healthcare giving, health education, mental health counseling, and environmental hygiene are essential health services required by students. However, the availability and utilization of these services are inadequate, affecting students' academic performance and overall well-being. The study recommends that tertiary institutions prioritize the provision of quality health services to support students' health and academic success.